Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3892/etm.2019.7458
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of the posterolateral approach of plate fixation for posterior pilon fractures

Abstract: Posterior pilon fracture is a common type of intraarticular fracture encountered in clinical practice. The treatment of this fracture pattern has been increasingly reported. However, methods for minimizing the associated surgical trauma and achieve effective fixation still require to be established. The present study involved 23 patients with posterior pilon fracture treated at the First Affiliated Hospital of Soochow University (Suzhou, China) between March 2013 and October 2017. Klammer's classification syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…The AOFAS score was significantly higher in the OFFL group than in the TPL group at the final followup (p = 0.037). Also using the traditional posterolateral approach, the anatomic repositioning rate was higher than the 53.8% of Klammer et al [2] and the 73.9% of Gao et al [11]. The AOFAS score was also higher than the 82 points of Klammer et al [2] and the 82.3 points of Gao et al [11].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The AOFAS score was significantly higher in the OFFL group than in the TPL group at the final followup (p = 0.037). Also using the traditional posterolateral approach, the anatomic repositioning rate was higher than the 53.8% of Klammer et al [2] and the 73.9% of Gao et al [11]. The AOFAS score was also higher than the 82 points of Klammer et al [2] and the 82.3 points of Gao et al [11].…”
Section: Discussionmentioning
confidence: 79%
“…Numerous surgical procedures are currently available to treat posterior pilon fractures, but posterior posterolateral is the most commonly used. This is because it allows one incision to fix the posterior and lateral ankle [2,[6][7][8][9][10][11]. The current surgical challenge is to adequately visualize the distal tibial fracture break and to deal with small bone fragments embedded in the fracture, such as die-punch bone fragments, cartilage pieces and soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used some of the same outcome measures to assess ankle function recovery after surgery for PMFs. For example, Gao et al reported on patients who underwent a posterolateral approach to reduction and plate fixation of posterior pilon fractures (19). They used the AOFAS score to assess ankle function recovery in 23 patients, and they found it to be 82.3 (range 44-97).…”
Section: Discussionmentioning
confidence: 99%